Uruguayan Cinema, 1960-2010: Text, Materiality, Archive - Lacruz, Cecilia (Imagofagia, 2021)
Sobre Beatriz Tadeo Fuica. Uruguayan Cinema, 1960-2010: Text, Materiality, Archive. Woodbridge: Tamesis, 2017, 180 pp., ISBN: 9781855663190.